Simultaneous determination of paracetamol and diclofenac in wastewater by high-performance liquid chromatography method - Nguyen Thanh Dong,; Nguyen Thi Thu Trang,; Nguyen Viet Hoang,; Pham Tuan Linh,; Pham Thi Yen, (Vietnam Journal of Science and Technology, 2023)
In this study, a simple, selective, and accurate analysis method was developed for the simultaneous determination of anti-inflammatory drugs (paracetamol and diclofenac) existing inlet and outlet of the wastewater treatment system. This method used solid-phase extraction (SPE) and reversed-phase high-performance liquid chromatography with a photodiode array detector (HPLC-PDA). Separation was performed using an HSR C18 column (250 mm × 4.6 mm; 5 µm) with a mobile phase consisting of acetonitrile: sodium dihydrogen orthophosphate in the ratio 60:40 v/v. The flow rate was 1 ml/min, and PDA was detected at 243 nm with paracetamol and 276 nm with diclofenac. The duration of paracetamol and diclofenac was 2.39 and 4.39 min, respectively. The developed method was validated in terms of accuracy, precision, and linearity for two drugs found in the range of 0.01 - 1 µg/ml, and 0.02 - 1 µg/ml for paracetamol, and diclofenac, respectively. The limits of detection for paracetamol and diclofenac were 0.003 µg/ml and 0.006 µg/ml, respectively, whereas the limits of quantification were 0.01 µg /ml and 0.02 µg/ml, respectively. The recoveries for paracetamol and diclofenac were greater than 95 %. The described method also has been applied to determine paracetamol and diclofenac simultaneously in the wastewater of the treatment system.